2018
DOI: 10.1111/jocn.14278
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspectives on basic nursing care education

Abstract: Improved basic nursing care will enhance nurse-sensitive outcomes and patient satisfaction and will contribute to lower healthcare costs. This study shows that there is scope within current nurse education in the Netherlands to focus more systematically and explicitly on basic nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
1
18
0
5
Order By: Relevance
“…Three types of knowledge Benner, Sutphen, Leonard, Day, and Shulman () highlight that the academic setting needs to focus on and integrate explicitly in nursing education in order for the knowledge and skills taught in school setting to become relevant to the students’ clinical practice. A study by Huisman‐de Waal et al concludes that fundamental care may best learned within clinical setting as opposed to theoretical education (Huisman‐de Waal, Feo, Vermeulen, & Heinen, ), which to some extent complements some of the results in this study. A study underlines that students do not necessarily perceive the academic staff as role models (Felstead, ), due to their distance from practical clinical nursing.…”
Section: Discussionsupporting
confidence: 74%
“…Three types of knowledge Benner, Sutphen, Leonard, Day, and Shulman () highlight that the academic setting needs to focus on and integrate explicitly in nursing education in order for the knowledge and skills taught in school setting to become relevant to the students’ clinical practice. A study by Huisman‐de Waal et al concludes that fundamental care may best learned within clinical setting as opposed to theoretical education (Huisman‐de Waal, Feo, Vermeulen, & Heinen, ), which to some extent complements some of the results in this study. A study underlines that students do not necessarily perceive the academic staff as role models (Felstead, ), due to their distance from practical clinical nursing.…”
Section: Discussionsupporting
confidence: 74%
“…We need sound economic evaluation of the investment required and to off set that with improvements in health outcomes, throughput, and safety and quality indicators. We need to research how we teach fundamental care to nursing students39–43 and we need to understand how fundamental care is embedded in policies and legislation at national and local levels 44…”
Section: Proposed Solution …mentioning
confidence: 99%
“…Within nursing education, Huisman‐de Waal, Feo, Vermeulen, and Heinen () explored nursing students' perspectives on basic nursing care education. Their results demonstrated that students face challenges in identifying a patient's care needs.…”
Section: Introductionmentioning
confidence: 99%